Geophysical characteristics and interpretation methods of the buried hill surface in the west slope of Shulu depression. Issue 4 (March 2021) - Ren, Chongyu; Lv, Hongjiu; Huang, Wenfeng; Liu, Bo; Zhao, Zhengquan
Abstract: In the cause of the buried hill and conglomerate layer are carbonate rock type, there is no obvious difference between the wave impedance and the overlying strata. Therefor there is no strong reflection on the surface of the buried hill, and no obvious change in the logging curve. In order to solve this problem, taking west slope of Shulu depression as an example, the logging characteristics of the conglomerate surface and seismic reflection characteristics of the buried hill surface are summarized. The sedimentological characteristics of the buried hill surface are analyzed. The differences between the identification of the buried hill surface and the identification of the conglomerate surface are found. The interpretation method of the buried hill surface is defined. It provides a theoretical basis for better interpretation of buried hill reservoir.